Perceptions of bankers on green banking practices and their role in promoting environmental sustainability in Nepal - Ghimire , Govind; Ojha , Sateesh Kumar; Tripathi , Yashodham (A Bi-annual South Asian Journal of Research & Innovation, 2026)
Green banking has become an important way to encourage environmental sustainability in the financial industry. Even while green banking is important all across the world, not much research has been done on how poor nations like Nepal use and think about it. This research examines bankers' perspectives of the advantages, efforts, and leadership qualities related to green banking, in addition to the organizations accountable for its effective implementation and the environmental risks it alleviates. We used a structured rating questionnaire to get data from 44 bankers, and then we used descriptive statistics and mean-based ranking approaches to look at the data. The results show that the most important advantages of green banking are environmentally friendly and sustainable financial operations. Ethical and principled banking is seen as less important. Ecological responsibility, resource efficiency, and conduct focused on sustainability are all signs of a good banker. Recycling rubbish and solar-powered branches are the most important green projects, whereas bio-gas plants and other infrastructure projects are less important. The research also shows that people see government and central bank authorities as the main groups responsible for developing green banking, while bankers themselves are seen as supporting players. Green banking is said to be the best way to deal with air pollution and waste management, and it also helps reduce greenhouse gasses and strange weather patterns in a roundabout way.The report gives policymakers, regulators, and banks useful information that they can use to create targeted strategies, incentives, and training programs that make green banking practices more popular and successful. Focusing on practical, environmentally friendly projects and helping bankers improve their skills will speed up sustainable growth in Nepal's banking sector.